Facile light-assisted preparation of reusable magnetic Fe3O4@SiO2@Chitosan composite for adsorption of dyes. (3rd July 2020) - Tang, Qi; Yang, Ting; Wang, Song; Cong, Hai-Lin; Yang, Xin-Rui; Shen, You-Qing; Yu, Bing
Abstract: Magnetic composites have been widely used in the area of wastewater treatment, which own the properties of simple and quick adsorption and separation functions. This article presented a cost-effective and chemically modified adsorbent (Fe3 O4 @SiO2 @Chitosan) based on a novel facile light-assisted technique for methyl orange (MO) removal. The characterization results of FT-IR, TEM, XRD and the hysteresis loop showed that Fe3 O4 @SiO2 @Chitosan was successfully prepared. The adsorption properties of the magnetic Fe3 O4 @SiO2 @Chitosan composite had been discussed in detail. Results show that the magnetic composite was able to remove more than 99.15% of dyes in water under optimized conditions. The Fe3 O4 @SiO2 @Chitosan composite was stable and easily recovered, which demonstrated that the Fe3 O4 @SiO2 @Chitosan can be successfully used as a reusable absorbent for effective removal of methyl orange from wastewater.